Screening of kidney disease in HIV infected hospitalised patients - Kumar, Sanjeev; Trivedi, Arvind; Aneja, G. K.; Atam, V; Arya, T.V.S.; Vandana, Dr.; Kumar, Pradeep (Asian Journal of Medical Sciences, 2014)
Objectives: To study the renal disease in newly diagnosed HIV infected hospitalized patients and to look for possible correlation of CD4 count with prevalence of renal disease. Materials and Methods: The prospective study was conducted in Department of Medicine/Endocrinology in tertiary care health center in western U.P during the study period of one year. The patients were evaluated clinically and biochemically after obtaining the informed consent. Result: The study was conducted on 100 HIV/AIDS patients, out of which 68 (68%) were males and 32 (32%) females with a Highest incidence of HIV/AIDS (51%) in the age group of 25-35 years. Microalbuminuria was present in 20 (20%) HIV patients with majority (60%) being in the age group 25-35 years. Prevalence of microalbuminuria among males was 55% and among females 45%. Microalbuminuria was further evaluated by calculating the ratio of microalbumin to urinary creatinine, 83% patient had ratio >10 mg/mmol and 17% had this ratio <10 mg/mmol. The ratio of microalbumin to urinary creatinine >10 mg/mmol was 60% in age 25-35 year, 25% in the age group of 36-45 year followed by 15% in the age group of 45-55 year patients. Chi-square test was used to calculate the significance of the correlation between CD4 counts with the presence of microalbuminuria in HIV patients. There was a significant correlation between CD4 count <200/μL and presence of microalbuminuria (p =0006). Statistically significant proteinuria (30-300 mg/24 hour) was found in 15 patients with CD4 count <200/μL of those patients found positive for microalbuminuria. Protein/ creatinine ratio was <0.2 in 18 patients, 2 had ratio in the range of 0.2-3.5 and none in the nephrotic range (>3.5). Conclusion: Study evaluation shows that there is statistically significant microalbuminuria in HIV/AIDS infected patients and this is more prevalent in patients with CD4 count <200/μL as compared to patients with CD4 count >200/μL in keeping with previous studies. The routine laboratory measurements like serum creatinine and proteinuria fail to recognize the patients with early renal involvement. In view of the high prevalence of renal dysfunction among hospitalized HIV infected patients, it is recommended to use microalbuminuria as routine screening tests in those who are HIV positive. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11376 Asian Journal of Medical Sciences Vol.6(3) 2015 58-62